2020
DOI: 10.1002/ima.22483
|View full text |Cite
|
Sign up to set email alerts
|

A fuzzy and spline based dynamic histogram equalization for contrast enhancement of brain images

Abstract: In general, medical images acquired at insufficient lighting conditions are suffering from low contrast issues which are inadequate for image analysis steps. One standard solution to improve the image contrast is to change its intensity distribution with the help of an image histogram. The histogram‐based contrast enhancement methods treat the images as regions rather than objects which would be more useful for applications like brain image enhancement. In this paper, a Fuzzy and Spline based Histogram Equaliz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 58 publications
(75 reference statements)
0
8
0
Order By: Relevance
“…Future studies can employ the suggested technique to enhance CT images. RF [18], (d) DIE [19], (e) FLSMF [14], (f) FSBDHE [15], (g) MCHE [16], and (h) Sug…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Future studies can employ the suggested technique to enhance CT images. RF [18], (d) DIE [19], (e) FLSMF [14], (f) FSBDHE [15], (g) MCHE [16], and (h) Sug…”
Section: Discussionmentioning
confidence: 99%
“…Figure . 8 MRI brain Images 37 enhanced by using several algorithms: (a) original , (b) LFE [17], (c) RF [18], (d) DIE [19], (e) FLSMF [14], (f) FSBDHE [15], (g) MCHE [16], and (h) Sug [17], (c) RF [18], (d) DIE [19], (e) FLSMF [14], (f) FSBDHE [15], (g) MCHE [16], and (h) Sug…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations